Functional nanocellulose films as fluorescent media - Indias, Johanna Mae M (Archīum Ateneo, 2018)
Fluorescent nanocellulose films fabricated via 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-mediated oxidation of cellulose nanofibers were prepared using two methods. In the first process, fluorescent particles were added halfway through the last vacuum filtration step of film fabrication. Three different particles were used: micro-pSi, micro-pSi with COOH, and Si-COOH nanocrystals. Several optical techniques were employed to characterize resulting films: UV-Vis spectrophotometry, fluorescence spectrophotometry, scanning electron microscopy (SEM), and Fourier transform infrared (FTIR) microscopy. All techniques revealed that particles retained their intrinsic properties after deposition on the film. Photoluminescence spectra of resulting films at λexcitation = 350 nm exhibited the following fluorescence peaks: λmicro-pSi = 600 nm, λmicro-pSi with COOH = 596 nm, λSi-COOH nanocrystals = 618 nm. A blue shift of at most 20 nm was observed when comparing particle fluorescence peak emission before and after deposition on the film. The peak shift was attributed to oxidation, as the particles remained in an aqueous solution during film fabrication. Continued observation of film fluorescence spectra showed that peak emission values are maintained for a month. A second method of fluorescent film fabrication involved the immersion of a dry, transparent nanocellulose film in a chlorophyll in acetone solution. Fluorescence spectra of the resulting hybrid film were taken using a UV laser as the excitation source (λexcitation = 355 nm). The fluorescence peak was found to be λchlorophyll = 683.21 nm. Both methods of film hybridization were effective in preparing nanocellulose films that show promise as stable fluorescent media.